Acute coronary syndrome among patients with chest pain: Prevalence, incidence and risk factors. (1st July 2016) - Baccouche, Houda; Belguith, Asma Sriha; Boubaker, Hamdi; Grissa, Mohamed Habib; Bouida, Wahid; Beltaief, Kaouthar; Sekma, Adel; Fredj, Nizar; Bzeouich, Nasri; Zina, Zied; Boukef, Riadh; Soltani, Mohamed; et al.
Abstract: Background: Urbanization and adoption of new diet and lifestyles had increased the cardiovascular risk factor (CVRF) rate and therefore, acute coronary syndrome (ACS) in developing countries such as Tunisia. We aimed at determining ACS prevalence among a sample of Tunisian patients with chest pain, at establishing the standardized incidence rate (SIR) of ACS, and at quantifying the relationship between ASC and CVRF in this population. Methods: We studied 3158 patients admitted to a chest pain unit for non-traumatic chest pain collected in Emergency Data from January 2012 to December 2014. For all patients, the data were collected using a standardized form. We performed univariate rather than multivariate logistic regression analyses to identify age and gender-related CVRF in ACS. Linear interpolation was used for curve estimation. Results: 707 (22.3%) chest pain patients were classified as ACS. The age-SIR per 10 − 5  person year (PY) was 85.7; it was 112.6 in men and 45.3 in women. Eighty one percent of patient with ACS cumulated 2 CVRF and more. The highest odds ratio were 2.00 (95% CI 1.64–2.44) for diabetes and 1.81 (95% CI 1.50–2.18) for active smoking. ACS in elderly patients was significantly associated with active smoking (OR: 2.36), diabetes (OR: 1.72) and personal ACS history (OR: 1.71). We found a significant and very high linear relation between the number of CVRF and ACS odds ratio (R 2  = 0.958). Conclusion: Our results showed that the incidence of ACS in a Tunisian population is not very different from what is observed in developed countries; with a close relation with CVRF especially diabetes and smoking.